Globalization Challenges Of A MNC : Effects Of Leadership And Motivation On Quality Performance Moderated By The Cultural Differences Between Malaysia And Vietnam - Lakshmanan, Vishva (2010)
This study aims to cover an area that has not been fully understood but which is gaining in importance in recent years. With the extent of globalization, it's without any doubt that companies would need to go beyond national shores in order to compete more effectively globally. Penyelidikan ini bertujuan untuk memahami suatu bidang yang tidak mempunyai pemahaman yang terperinci, tapi yang semakin penting kini. Dengan globalisasi yang semakin memain peranan penting, tidak dinafikan yang lebih syarikat terpaksa merantau ke negara lain untuk bersaing dengan lebih berkesan.